Airway management during cardiopulmonary resuscitation. Issue 3 (June 2015) - Bernhard, Michael; Benger, Jonathan R.
<x xml:space="preserve">Abstract</x> Purpose of review This article evaluates the latest scientific evidence regarding airway management during in-hospital and out-of-hospital cardiopulmonary resuscitation (CPR). Recent findings In the in-hospital setting, observational research suggested that the quality of CPR using 'no flow ratio' as a surrogate marker was improved when advanced airway techniques were used. A registry study demonstrated that an initial failed intubation attempt was associated with an average delay of 3 min in time to return of spontaneous circulation. A prospective observational study showed that the Glide Scope videolaryngoscope was associated with a first-pass success rate of 93%, with no differences between less and more experienced physicians. In the out-of-hospital setting, a registry study suggested that intubation leads to a better outcome compared with supraglottic airway devices. However, no advanced airway devices showed a better outcome than basic airway techniques. An observational study reported that the i-gel supraglottic airway device offers a first-pass insertion success rate of 90%, and was easier to establish than the Portex Soft Seal laryngeal mask airway. Other out-of-hospital observational studies showed that the laryngeal tube offers a lower first-pass insertion success rate than expected, and complications of this device may influence later definitive airway management and the outcome as a whole. Summary Recent studies of airway management during CPR rely mostly on registry and observational designs. Prospective randomized trials are needed to determine the optimal approach to airway management during cardiac arrest, but have not yet been completed.